MCL-1 Inhibition Overcomes Anti-apoptotic Adaptation to Targeted Therapies in B-Cell Precursor Acute Lymphoblastic Leukemia - Manzano-Muñoz, Albert; Alcon, Clara; Menéndez, Pablo; Ramírez, Manuel; Seyfried, Felix; Debatin, Klaus-Michael; Meyer, Lüder H.; Samitier, Josep; Montero, Joan (Frontiers in Cell and Developmental Biology, 2021)
Multiple targeted therapies are currently explored for pediatric and young adult B-cell precursor acute lymphoblastic leukemia (BCP-ALL) treatment. However, this new armamentarium of therapies faces an old problem: choosing the right treatment for each patient. The lack of predictive biomarkers is particularly worrying for pediatric patients since impairs the implementation of new treatments in the clinic. In this study, we used the functional assay dynamic BH3 profiling (DBP) to evaluate two new treatments for BCP-ALL that could improve clinical outcome, especially for relapsed patients. We found that the MEK inhibitor trametinib and the multi-target tyrosine kinase inhibitor sunitinib exquisitely increased apoptotic priming in an NRAS-mutant and in a KMT2A-rearranged cell line presenting a high expression of FLT3, respectively. Following these observations, we sought to study potential adaptations to these treatments. Indeed, we identified with DBP anti-apoptotic changes in the BCL-2 family after treatment, particularly involving MCL-1 - a pro-survival strategy previously observed in adult cancers. To overcome this adaptation, we employed the BH3 mimetic S63845, a specific MCL-1 inhibitor, and evaluated its sequential addition to both kinase inhibitors to overcome resistance. We observed that the metronomic combination of both drugs with S63845 was synergistic and showed an increased efficacy compared to single agents. Similar observations were made in BCP-ALL KMT2A-rearranged PDX cells in response to sunitinib, showing an analogous DBP profile to the SEM cell line. These findings demonstrate that rational sequences of targeted agents with BH3 mimetics, now extensively explored in clinical trials, may improve treatment effectiveness by overcoming anti-apoptotic adaptations in BCP-ALL.